A path to better mental health among emerging adults: forgiveness as a solution to interpersonal conflicts - Bonete, Saray; Molinero, Clara; Sendra, Susana; González De Abreu, Anna Mariela (Frontiers in Psychology, 2025)
The present study offers insight into the importance of forgiveness in the holistic development of university students, through an empirical analysis of forgiveness associated with variables related to well-being such as self-esteem, hope, depression, anxiety, stress and anger among Spanish students (n = 463). The aim was to identify the needs of the group and to explore the relationship between forgiveness and these variables. A quantitative analysis was conducted using a battery of questionnaires. Pearson correlations and one-way ANOVA tests were performed. Results showed significant positive relationships between forgiveness, self‑esteem, and hope, and negative relationships with depression, anxiety, stress, and anger. Students with higher forgiveness levels showed significantly greater self-esteem and hope and lower depression and anger than those with lower forgiveness levels. This research tentatively highlights the need to implement forgiveness programs to improve university students’ skills, promote psychological well‑being, and facilitate positive adaptation to the workplace.